2009
DOI: 10.1111/j.0105-2896.2009.00853.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to citrullinated proteins: molecular interactions and arthritogenicity

Abstract: The discovery of antibodies specific for citrullinated protein epitopes [anti-citrullinated protein antibodies (ACPAs)] is a hallmark for the diagnosis and prognosis of rheumatoid arthritis (RA) and will also be a useful tool for understanding the fundamental pathologic processes. There are several essential questions pertaining to ACPA that remain to be explored, such as understanding the early specificity of the underlying T-cell recognition, whether the production of ACPA is a primary or secondary process, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 229 publications
(294 reference statements)
2
62
0
1
Order By: Relevance
“…Studies in RA patients (1,10,11) and animal models of arthritis (43) have revealed the pathogenic effects of antibodies. Antibodies against type II collagen (43, 44) and glucose-6-phosphate isomerase (45) are examples of pathogenic antibodies as revealed in mice with collagen-induced arthritis and K/BXN mice, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in RA patients (1,10,11) and animal models of arthritis (43) have revealed the pathogenic effects of antibodies. Antibodies against type II collagen (43, 44) and glucose-6-phosphate isomerase (45) are examples of pathogenic antibodies as revealed in mice with collagen-induced arthritis and K/BXN mice, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of anti-citrullinated protein antibodies (ACPA) is a unique feature of rheumatoid arthritis (RA) (1,2). Citrullinated proteins are generated by deimination catalyzed by peptidyl arginine deiminases (PADs), including PAD1-4 and PAD6 (3).…”
Section: Introductionmentioning
confidence: 99%
“…3 Antibodies to citrullinated proteins are among the most specific described in RA and are believed to play a role in the pathogenesis of the disease. [4][5][6][7][8] These antibodies were originally identified by Schellekens et al, 9 who described specific antibody reactivity to a profilaggrin peptide containing the modified amino acid citrulline. The post-translational generation of citrulline, referred to as citrullination or deimination, is a modification of the side chain of arginine, where the guanidino group is replaced by an ureido group.…”
Section: Introductionmentioning
confidence: 99%
“…4,10 Antibodies specific for citrullinated proteins recognize a variety of citrullinated autoantigens, including a-enolase, fibrinogen, type II collagen, and vimentin, and are collectively identified as anticitrullinated peptide/protein antibodies (ACPA). [11][12][13][14][15] These ACPA responses, primarily characterized by IgG 1 and IgG 4 subtypes (99 and 98% of ACPA-positive RA patient sera, respectively), have been found to be present up to years before disease onset and to be highly specific (98%) and sensitive (up to 80%) for RA. [16][17][18][19][20][21] Thus, APCA are used as a supplement to clinical diagnosis of RA.…”
Section: Introductionmentioning
confidence: 99%